Errors Associated With Medication Administration by a Nurse During Hospitalisation: A Prospective Observational Multicentric Study - Ondrej Tesar; Martin Dosedel; Ales Antonin Kubena; Katerina Mala‐Ladova; Radka Prokesova; Iva Brabcova; Hana Hajduchova; Martin Cerveny; Ivana Chloubova; Jiri Vlcek; Valerie Tothova; Josef Maly (Nursing Open)
ABSTRACT Aims To explore all medication administration errors (MAEs) throughout the entire process of medication administration by nurses in the inpatient setting, to describe their prevalence, and to analyse associated factors, including deviation from the good practice standards. Background Worldwide, MAEs are very common and regarded as a serious risk factor to inpatient safety. Nurses assume an essential role in the hospital setting during the administration of medications. Design The prospective observational study was carried out in accordance with the STROBE guidance. Methods This study was conducted in four regional hospitals from June to August 2021. MAEs were collected when nurses administered medications to the adult inpatients during the morning, noon, and evening medication rounds at the internal, surgical, and follow‐up care departments in each hospital over three consecutive days. Direct observation by the multidisciplinary team was employed. MAEs were classified as major MAEs (from the potentially most serious and common to all drug forms), specific MAEs (specific to a drug form), and procedural MAEs (e.g., patient identification, hygiene standards, or generic drug substitution). Predictors of either major MAE or specific MAE frequency were analysed using the generalised linear model and the decision tree model. Results Overall, 58 nurses administering medication to 331 inpatients at 12 departments were observed. In total, 6356 medication administrations were observed, of which 461 comprised major MAEs, 1497 specific MAEs, and 12,045 procedural MAEs. The predictors of the occurrence of major MAEs and specific MAEs were the specific hospital, the nurse's length of practice (less than 2 years), and two procedural MAEs (the unclear prescription and the wrong strength). Conclusions Non‐adherence to the standard processes in healthcare facilities for prescribing and administering drugs increased the prevalence of severe MAEs. Determinants of MAE occurrence such as incorrect prescriptions or limited experience of nurses should be considered. Implication for the Profession and Patient Care The identified determinants of MAE should be considered by hospital stakeholders in their support programs to reduce the level of burden for nurses during medication administration. Patient or Public Contribution Neither patients nor public was not involved in the design, data collection, or dissemination plans of this study. The researchers observed nurse care delivery at medical departments acting as passive participants.